2021
DOI: 10.1038/s41598-021-03698-7
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of arterial spin labeling perfusion as an initial evaluation of status epilepticus

Abstract: This study aimed to evaluate the sensitivity and prognostic value of arterial spin labeling (ASL) in a large group of status epilepticus (SE) patients and compare them with those of other magnetic resonance (MR) sequences, including dynamic susceptibility contrast (DSC) perfusion imaging. We retrospectively collected data of patients with SE in a tertiary center between September 2016 and March 2020. MR images were visually assessed, and the sensitivity for the detection of SE and prognostication was compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…20 This study demonstrated that relevant changes in ASL were observed in 90% of patients with status epilepticus, while only 41% of patients had self-limiting seizures. 20 Our findings are also consistent with findings that prolonged seizures are more likely to be focal. 16,21 Strong correlations between focality and prolonged duration have been reported in FS.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…20 This study demonstrated that relevant changes in ASL were observed in 90% of patients with status epilepticus, while only 41% of patients had self-limiting seizures. 20 Our findings are also consistent with findings that prolonged seizures are more likely to be focal. 16,21 Strong correlations between focality and prolonged duration have been reported in FS.…”
Section: Discussionmentioning
confidence: 57%
“…Our results are consistent with those of a previous study that compared ASL perfusion between status epilepticus and self-limiting seizures. 20 This study demonstrated that relevant changes in ASL were observed in 90% of patients with status epilepticus, while only 41% of patients had self-limiting seizures. 20 Our findings are also consistent with findings that prolonged seizures are more likely to be focal.…”
Section: Discussionmentioning
confidence: 57%
“…Recent advances in arterial spin labeling (ASL) have made it feasible to measure blood vessel diameter using MRI, which is advantageous over ictal SPECT in that it requires no radioactive dyes and is high resolution. Indeed, a newly published retrospective study 7 and several recent papers [8][9][10] support the notion that ASL MRI is useful for establishing prognosis and localizing a focus in patients with epilepsy, although the predictive power of ASL depended on how soon after a seizure images were acquired.…”
Section: Commentarymentioning
confidence: 98%
“…94 In patients with status epilepticus, ongoing seizure activity may yield lead to diffuse cerebral hyperperfusion with excitotoxic complications. 95,96 In patients with chronic epilepsy, MDASL can be helpful for longitudinal CBF quantification to assess treatment response (both medical and surgical).…”
Section: Epilepsymentioning
confidence: 99%